Custos em empresas de serviços ambientais: estudo de caso - Tsurumaki, Kazuyochi (2008)
The study has as main objective explore the characteristics of the activities of services and understand how they should be handled by systems cost, as the scenario of the world economy in recent decades has led the service sector to a level higher than the sectors of industry and Agriculture. In other words, services are the activities that most grew in most developed and developing countries highlighting itself as an activity generator of wealth. Thus, it is necessary to the understanding of the major systems of cost and identifying the differences between the product service and product manufacturing. Through analysis of the system of funding of Ecosorb SA Tecnologia em Proteção Ambiental, object of case study, it was possible, using interviews, verification of documents and analysis of reports, understand premises, attributes and operation of the system costing adopted by the company. The economic development and globalization have created a competitive environment and therefore the market has become more disputed. In this environment, companies that have a need to control their costs have a competitive advantage and survival